2021
DOI: 10.1126/science.abi8532
|View full text |Cite
|
Sign up to set email alerts
|

Modular polyketide synthase contains two reaction chambers that operate asynchronously

Abstract: Big molecules build small Actinomycete bacteria are prolific producers of bioactive small molecules such as polyketide antibiotics. These molecules are built by the addition of short carbon units to a growing, protein-tethered chain, either iteratively as in fatty acid synthesis or in a modular fashion by a hand-off from one distinct enzyme complex to the next. Bagde et al . and Cogan et al . report structures of polyketide synthase modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 55 publications
(33 reference statements)
8
68
0
7
Order By: Relevance
“…This work revealed that interdomain contacts are critical for establishing the various functional states of the module, and that transitions between such states rely on evolving interfaces between the domains, as well as the intervening ‘linker’ regions. This view of modular function was recently reinforced by cryo-EM/crystallographic analysis of additional modules sourced from two PKS systems 6 , 7 . In short, PKS modules appear to be highly integrated units, thus explaining why exchange of catalytic domains for heterologous counterparts is often detrimental 8 .…”
Section: Introductionmentioning
confidence: 95%
“…This work revealed that interdomain contacts are critical for establishing the various functional states of the module, and that transitions between such states rely on evolving interfaces between the domains, as well as the intervening ‘linker’ regions. This view of modular function was recently reinforced by cryo-EM/crystallographic analysis of additional modules sourced from two PKS systems 6 , 7 . In short, PKS modules appear to be highly integrated units, thus explaining why exchange of catalytic domains for heterologous counterparts is often detrimental 8 .…”
Section: Introductionmentioning
confidence: 95%
“…This contact area is smaller than those of previously reported trans-AT-ACP complexes such as the VinK-VinL structure (Miyanaga et al, 2016; $650 A ˚2) and the DSZS AT-ACP1 structure ($600 A ˚2; Miyanaga et al, 2018). It is also smaller than that of the Lsd14 AT-ACP complex ($610 A ˚2; Bagde et al, 2021), but is larger than that of the FabD-AcpP complex ($350 A ˚2; Misson et al, 2020) (Fig. 3).…”
Section: The At Large Subdomain Serves As a Major Binding Platform Fo...mentioning
confidence: 58%
“…Comparison with the AT-ACP of apo Lsd14 reveals different features (Bagde et al, 2021;Supplementary Fig S15). The distance between the catalytic Ser657 of LsdAT7 and Ser1526 of LsdACP7 is 22.5 A ˚, but this distance is 17.9 A ˚in the SalAT9M-ACP9 complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 The possible cooperativity of the homodimeric type II KS has rarely been addressed, but cooperativity effect has recently been reported in the type I murine KS domain, as well as a type I PKS. 67,68 Despite the lack of activity towards C16 SFA, EcFabF elongates C16:1 UFA, producing the C18:1 acid that could be incorporated into membrane phospholipids to increase cell membrane fluidity. 69,70 It has been demonstrated in vitro and in vivo that FabF plays a key role in the thermal regulation of E. c o li b y it s s u b s tr a t e p re f e r e n c e s u n d e r d i ff e r en t temperature.…”
Section: The Dichotomy Of Fabf and Fabbmentioning
confidence: 99%